Satisfactory outcomes from the double-row fixation procedure for ankle lateral ligaments injury with os subfibulare - Hong-Yun Li; Wen-Kai Xuan; Hong-Yue Tao; Hong Li; Ying-Hui Hua; Shi-Yi Chen (Elsevier, 2024)
Background: Ossicles of avulsed fractures of the lateral malleolus can result in pain or chronic ankle instability. The purpose of this study was to evaluate and compare the arthroscopic double-row fixation procedure with anatomic ankle lateral ligaments reconstruction for the treatment of ankle lateral ligaments injury with os subfibulare. Methods: This retrospective study included 38 patients with ankle lateral ligaments injury with concomitant os subfibulare who were treated between July 2016 and November 2021. The patients were divided into a double-row fixation group (n = 19) and an ankle lateral ligaments reconstruction group (n = 19). The Karlsson and Peterson Scoring System for Ankle Function (KAFS), American Orthopedic Foot and Ankle Society (AOFAS) score, Tegner score, visual analog scale (VAS), and anterior drawer test (ADT) were obtained preoperatively and at the last post-operative follow-up. Magnetic resonance imaging (MRI) was also performed at the last post-operative follow-up. Results: The KAFS, AOFAS, VAS, and Tegner scores increased significantly after the surgery. Furthermore, the pre- and post-operative functional scores were comparable between the two groups. The ADT was negative in all participants post-operatively. There were no significant differences between the double-row fixation and ligaments reconstruction groups regarding the proportions of patients who achieved a minimally clinically important difference (MCID) in KAFS, AOFAS, and Tegner scores. There was no significant difference in T2 mapping values for the tibial and talar side post-operatively between the two groups. Moreover, there were no significant differences in functional scores post-operatively between bony fusion and non-fusion patients in the double fixation group. Conclusion: The double-row fixation procedure provided similar satisfactory clinical outcomes when compared with lateral ligaments reconstruction for the treatment of ankle lateral ligaments injury with os subfibulare over a short follow-up duration.